2016
DOI: 10.1017/cem.2016.344
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Analysis of Salbutamol Administration by Metered-Dose Inhalers with Spacers versus Nebulization for Patients with Wheeze in the Pediatric Emergency Department: Evidence from Observational Data in Nova Scotia

Abstract: Background: Despite evidence demonstrating the advantages of metered-dose inhalers with spacers (MDI-s), nebulization (NEB) remains the primary method of asthma treatment in some pediatric emergency departments (PEDs). There is a perception that delivering salbutamol by MDI-s is more costly than by NEB. This research evaluates the relative costs of MDI-s and NEB using local, hospital-specific, patientlevel data. Methods: Regression models estimated associations between the salbutamol inhalation method and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The exacerbations account for the majority of asthma‐related costs and had a negative impact in the quality of life and education in children with asthma . Also, many studies showed that the use of MDIs with spacers instead of nebulizers to deliver beta‐2 agonist to treat children with mild‐to‐moderate asthma exacerbations in the ED could yield significant cost savings for hospitals and, by extension, to both the health care system and families of children with asthma …”
Section: Discussionmentioning
confidence: 99%
“…The exacerbations account for the majority of asthma‐related costs and had a negative impact in the quality of life and education in children with asthma . Also, many studies showed that the use of MDIs with spacers instead of nebulizers to deliver beta‐2 agonist to treat children with mild‐to‐moderate asthma exacerbations in the ED could yield significant cost savings for hospitals and, by extension, to both the health care system and families of children with asthma …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed a significant cost saving with MDIs/VHCs because patients improved faster, were sent home more quickly, and could be taught in the emergency department to use the MDIs/ VHCs, thus decreasing early readmission. 4,5 VHCs have numerous additional advantages including an up to 80% decrease in the upper respiratory tract deposition of inhaled medication, and generation of significantly smaller particles that better penetrate into the lung periphery. 3 Furthermore, they are totally self-contained and do not require an external, expensive, and bulky source of energy.…”
Section: Covid-19: Time To Embrace Mdi1 Valved-holding Chambers!mentioning
confidence: 99%
“…Research to date has shown that SABA as well as the combination of SABA and SAMA used in aerosol therapy of respiratory diseases may differ not only in the method of administration, but also in clinical effectiveness, safety and costs associated with their use in patients [3][4][5][6][7][8][9]. Research results indicate that regardless of the calculation method, the use of SABA with pMDI in combination with a valved holding chamber (VHC) instead of NEB is associated with a reduction in total costs in both the emergency department and the hospital ward [10][11][12][13][14][15]. There has been no similar analysis carried out in Poland.…”
Section: Introductionmentioning
confidence: 99%